An investigation into the influence of cross-cultural awareness on learning English verb tenses and aspects of 10th form students at Đong Son I high school, Thanh Hoa province = Nghiên cứu ảnh hưởng của nhận thức giao văn hóa trong quá trình học các thì v - Phạm, Thị Duyên (University of Languages and International Studies, 2017)
65 p. + CD-ROM